The next generation of synthetic cannabinoids: Detection, activity, and potential toxicity of pent‐4en and but‐3en analogues including MDMB‐4en‐PINACA. Issue 2 (5th October 2020) - Krotulski, Alex J.; Cannaert, Annelies; Stove, Christophe; Logan, Barry K.
Abstract: A new class of synthetic cannabinoids has emerged as new psychoactive substances (NPS). Similar in structure to JWH‐022, these substances contain alkene modifications to the tail region of the synthetic cannabinoid core structure, and nomenclature denotes these new analogues as pent‐4en or but‐3en species. Internationally, two analogues from this new series recently emerged: MDMB‐4en‐PINACA and MMB‐4en‐PICA. Previously, data regarding activity and potential toxicity were not available. In vitro assessment of cannabinoid receptor 1 (CB1) activation via the β‐arrestin 2 recruitment was studied for three (3) pent‐4en analogues, one (1) but‐3en analogue, and one (1) principal metabolite. MDMB‐4en‐PINACA (2.47 nM, 239%), MDMB‐4en‐PICA (11.5 nM, 302%), and MDMB‐3en‐BINACA (14.3 nM, 286%) were highly potent and efficacious (comparison: JWH‐018, 25.3 nM, 100%), while the potencies of MMB‐4en‐PICA and MDMB‐4en‐PINACA 3, 3‐dimethylbutanoic acid were markedly lower. Modifications to core and tail structural features (i.e., indole vs. indazole) led to relatively small differences in potency, while changes among the head region led to larger differences. Sample‐mining and data‐mining conducted on toxicology samples led to the identification of MDMB‐4en‐PINACA in 25 forensic toxicology cases, including postmortem and impaired driving investigations, with case details and limited histories described herein. Moderate geographical distribution of MDMB‐4en‐PINACA was noted in the United States with emergence in the Northeast, Midwest, South, and West regions. Results from toxicology testing paired with case history show the potential for MDMB‐4en‐PINACA to cause or contribute to impairment or death. Forensic scientists, public health and public safety officials, law enforcement, clinicians, medical examiners, and coroners should consider involvement of emergent synthetic cannabinoids in their work and that new analogues containing an alkene tail can retain similar or increased potency and toxicity. Abstract : As new psychoactive substance (NPS) markets evolve, so do the chemistries of the drugs detected. Synthetic cannabinoids represents one of the most diverse classes, as new substances emerge rapidly. The latest analogues contain alkene modifications to the tail region and are noted pent‐4en and but‐3en. Herein, we studied their activity as well as their positivity. MDMB‐4en‐PINACA was the most potent and the most commonly encountered analogue, appearing in several forensic investigations (e.g., postmortem and DUID).